Development of a Learning Module on Pantun Poetry with Global Diversity Awareness to Improve Learning Outcomes of 7th Grade Students - Husniyatul Adibah Alwaliyah; Agus Nuryatin; Nas Haryati Setyaningsih (Universitas Negeri Semarang, 2024)
Analysis of the teaching materials used by students in pantun learning during the early phase D, grade 7 of junior high school, semester 1, showed that the explanation of pantun material was very limited, and the practice questions used to assess students' understanding were also scarce. Additionally, the integration of character education content in pantun teaching materials was lacking. This highlighted the need for the development of a pantun learning module with a global diversity perspective. This study aimed to (1) analyze the needs for a module in pantun learning, and (2) develop a prototype of a pantun learning module with global diversity awareness. The research and development design were divided into seven stages, namely preliminary survey, initial prototype development, product design, product validation, design improvement, limited trial, and final design improvement. The results of this study indicated that the created module prototype was suitable for use as a teaching material in pantun learning. This was evident from the average validation scores of 88.5 from experts, which fell under the